Healthcare Practitioner Behaviours That Influence Unsafe Use Of Hospital Information Systems - Salahuddin, Lizawati; Hashim, Ummi Rabaah; Ismail, Nor Haslinda; Raja Ikram, Raja Rina; Ismail, Zuraini; Abdul Rahim, Fiza; Hassan, Noor Hafizah (SAGE Publications Ltd, 2019)
This study aims to investigate healthcare practitioner behaviour in adopting Health Information Systems which could affect patients’ safety and quality of health. A qualitative study was conducted based on a semi-structured interview protocol on 31 medical doctors in three Malaysian government hospitals implementing the Total Hospital Information Systems. The period of study was between March and May 2015. A thematic qualitative analysis was performed on the resultant data to categorize them into relevant themes. Four themes emerged as healthcare practitioners’ behaviours that influence the unsafe use of Hospital Information Systems. The themes include (1) carelessness, (2) workarounds, (3) noncompliance to procedure, and (4) copy and paste habit. By addressing these behaviours, the hospital management could further improve patient safety and the quality of patient care.